Pengaruh Pemberitaan Kekerasan Seksual pada Platform Instagram terhadap Siswa SMK Negeri 1 Batang - M Kholis Dwi Saputro (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2024)
Currently, the Indonesian government is focusing on using social media, especially Instagram, to fulfill their information needs; almost all local governments in Indonesia use social media to communicate with the public. This is followed by an increase in internet and social media usage in Indonesia. The researcher used quantitative research methodology by distributing questionnaires to respondents through the Counseling Guidance Teacher which was then distributed to students at SMK Negeri 1 Batang. The data analysis techniques used in this research are descriptive analysis, t hypothesis test, simple linear regression analysis and coefficient of determination. The results of the study based on the t hypothesis test, simple linear regression analysis, the coefficient of determination, provide results that the variable use of social media (X) has a significant negative effect on the mental variable of children (Y).